University-Based Collaborative Pre-service-Mentor Teacher Teams: A Model for Classroom-Based Inquiry - Ronald Beebe; Diane Corrigan (Networks: An Online Journal for Teacher Research, 2013)
Current literature indicates classroom inquiry not only enhances the training of pre-service teachers but also increases the effectiveness of mentor teachers and improves student learning. However, designing an effective collaborative model has met with less success. This study examined the experiences of ten pre-service/mentor teacher teams in urban schools who participated in designing and implementing collaborative classroom-based research conducted in their classroom. The model sought to address issues noted in previous studies related to equal participation and anxiety surrounding the research process. Findings suggest that a university supported model employing a reflective practitioner approach enhances collaboration and promotes positive results for both pre-service and in-service teachers. Specifically, participants indicated the importance of collaboration, engagement with the teaching process, heightened awareness of student learning, and professional efficacy as significant outcomes.